Ecocentric governance: Sustainability between the availability of resources and needs - Guillén, Javier Carreón; Aguayo, José Marcos Bustos; Vázquez, Francisco Rubén Sandoval; Lirios, Cruz García (Universitas Majalengka, 2022)
The objective of this study was to corroborate the dimensions of ecocentric governance: conflict between authorities and users, negotiation and agreement between the parties, and co-responsible self-regulation between the rulers and the ruled regarding energy and water resources and services. An exploratory, cross-sectional and psychometric study was carried out with a non-probabilistic selection of 100 officials and users of the electricity and water service. The Governance Inventory was used, and the three preponderant factors were obtained: conflict, negotiation-consensus, and self-regulation-co-responsibility. In relation to the literature consulted, the three factors refer to governance oriented towards resource conservation. The third factor of self-regulation and co-responsibility suggests policies oriented by the availability of energy and water resources. Empirical testing of the model in a scenario and a sample exposed to resource scarcity is recommended.